136k views
1 vote
Please help thank you!!!​

Please help thank you!!!​-example-1
User Futureal
by
4.8k points

2 Answers

5 votes

Answer:

y = -180 + 3x

Explanation:

Because AB = AC -> ABC is a isosceles triangle -> B = C

Because AB = BD -> ABD is an isosceles triangle -> A = D -> x = D

We have ADB + ADC = 180 -> x + ADC = 180 -> ADC = 180 - x (1)

We have x = D, and BAD + ADB + ABD = 180 -> ABD = 180 - 2x but B = C -> C = 180 - 2x (2)

With (1) and (2) We have DAC + ACD + ADC = 180

-> y + 180 -2x + 180 -x = 180

-> y + 360 - 3x = 180

-> y = -180 + 3x

User Marson Mao
by
4.8k points
3 votes

Answer:

y=3x-180

Explanation:

Above working is my step by step solution. Thank you.

Please help thank you!!!​-example-1
User Cystbear
by
4.8k points